As práticas jornalísticas na imprensa regional: a selecção das fontes e a promoção de desigualdades sociais - Morais, Ricardo (2013)
The regional press has emerged, especially in recent years, as a mean able to revalue the expression of multiple forms of journalism, with particular reference to the idea of closeness news. It is this enhanced role of the regional press, in its relationship with the public, which may constitute a real alternative to mass media. As an alternative, being closer to the people, their problems, these media constitute themselves as the main drivers of the "public space" and the "public sphere". Based on these characteristics, in this paper we analyze specifically the collection of information in its various stages, from the relationship with the sources, the pressures, constraints and criteria, inquiring about the possibility of the media constitute themselves as regional mechanisms makers and enhancers of inequalities in civic participation of citizens / readers. The starting point for the analysis lies in the practice of regional journalism, rather in the selection of sources, but also in the asymmetric distribution of resources, particularly resources of power and civic participation among various social groups that represent a predisposition for civic participation in "public space".